Movements Toward Living Relationally Ethical Assessment Making: Bringing Indigenous Ways of Being, Knowing, and Doing Alongside Narrative Inquiry as Pedagogy - Cardinal, Trudy; Murphy, M. Shaun; Huber, Janice (Revista Interuniversitaria de Formación del Profesorado. Continuación de la antigua Revista de Escuelas Normales, 2019)
As teacher educators deeply committed to relational narrative inquiry and the centrality of living in relationally ethical ways alongside co-researchers, our initial turns toward living narrative inquiry as pedagogy were inspired by wanting to live in relationally ethical ways alongside undergraduate and graduate students. Following the sudden passing in 2015 of Singing Turtle Woman—Anishinabe kweElder, scholar, and long-time friend and research collaborator Mary Isabelle Young, we often told and retold stories of how her teachings of Pimosayta (learning to walk together) and Pimatisiwin (walking in a good way) were continuing to guide us. In this midst we gradually realized that Mary’s teachings opened potential in conjunction with our desires to live/practice relationally ethical assessment making alongside students. As we engage in autobiographical narrative inquiry into our recent coming alongside undergraduate and graduate students, in two Assessment as Pimosayta courses in two differing teacher education programs in Canada, we show how our bringing Indigenous ways of being, knowing, and doing alongside our practicing narrative inquiry as pedagogy supported our movements toward living relationally ethical assessment making.